Comparison of multiplex cytokine assays in a pediatric cohort with epilepsy. Issue 3 (March 2021) - Numis, Adam L.; Fox, Christine H.; Lowenstein, Daniel J.; Norris, Philip J.; Di Germanio, Clara
Abstract: Background: Multiplex analyses allow for detection of dozens of cytokines/chemokines in small sample volumes. Although several commercially available assay kits are available, there are no comparative data in plasma measurements among pediatric or epilepsy cohorts. New method: Cohort study of 38 children with epilepsy. We evaluated plasma levels of cytokines/chemokines using three different assays: Luminex® xMAP high-sensitivity (HS) and standard-sensitivity (SS) assays, and Meso-Scale Discovery (MSD). We calculated recovery rates of each analyte, correlation coefficients between assays, and level of agreement between measurements. We repeated analyses in a subset of samples after a single freeze-thaw cycle. Results: Among ten analytes common to all assays, HS had high recovery (<15% of values extrapolated or out-of- range [OOR]) for all analytes, SS for 50%, and MSD for 40%. While several analytes had a high correlation between assays, Bland-Altman plots demonstrated assays were not interchangeable. For most analytes, a single freeze-thaw cycle decreased cytokines/chemokine measurements. There was good correlation of measurements after a freeze-thaw cycle with acceptable agreement between measurements for six of 13 (46%) analytes using HS, one of 9 (11%) for SS, and none for MSD. Comparison with existing methods: HS assays may optimize yield in plasma for proteins of particular interest in epilepsy research, limit values extrapolated beyond the standard curve, and improve precision compared to other SS and MSD assays. Conclusion: Our results demonstrate assay choice may be critical to study results and support the need for a standardized approach to biomarker assessment across epilepsy research and other domains. Abstract : Pediatric epilepsy, Cytokines, Chemokines, Luminex, Meso-scale discovery, Neuro-inflammation.